1997
DOI: 10.1046/j.1537-2995.1997.37197176949.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular background of VS and weak C expression in blacks

Abstract: It is therefore postulated that the hybrid gene is responsible for the weak expression of C in these individuals. The hybrid gene carried a Leu62Phe substitution, as well as the Leu245Val substitution responsible for VS. The gene most probably cosegregates with a C allele encoding Cys 16 (normally encoded only by the C allele) and Val245 (responsible for VS antigenicity when encoded by the RHCE gene). This explains the combination of weak expression of C and VS positivity that is frequently found in blacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
164
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(181 citation statements)
references
References 18 publications
13
164
2
2
Order By: Relevance
“…28 Amino acid substitutions that cause loss of epitopes in partial RH variants may be also associated with expression of new antigens referred to as "low-incidence" antigens because of their prevalence in the white reference population (Table 1). In blacks, some are highly prevalent, such as the RH20 (VS) antigen, encoded by the RHCE*ce S allele, 29 which is expressed in approximately 26% to 40% of persons of African origin. VS-negative SCD patients receiving blood from donors of same ethnic background can be potentially immunized to VS, but antibodies against VS are not routinely detected by screening tests because most test RBC reagents do not express VS.…”
Section: Rbc Alloimmunization Pathobiologymentioning
confidence: 99%
“…28 Amino acid substitutions that cause loss of epitopes in partial RH variants may be also associated with expression of new antigens referred to as "low-incidence" antigens because of their prevalence in the white reference population (Table 1). In blacks, some are highly prevalent, such as the RH20 (VS) antigen, encoded by the RHCE*ce S allele, 29 which is expressed in approximately 26% to 40% of persons of African origin. VS-negative SCD patients receiving blood from donors of same ethnic background can be potentially immunized to VS, but antibodies against VS are not routinely detected by screening tests because most test RBC reagents do not express VS.…”
Section: Rbc Alloimmunization Pathobiologymentioning
confidence: 99%
“…Sequences from chimpanzee (Pan troglodytes Rh-like protein IIR, nucleic acid accession number L37050 23 ) were used for external rooting. The RHD alleles shown in the phylogeny tree were published previously 13,14,[16][17][18][24][25][26][27][28][29][30][31] or described in this study for DAU-0 to DAU-4 and DIII type 5.…”
Section: Phylogeny Of Rhd Allelesmentioning
confidence: 99%
“…11 Molecular analysis revealed that there are often multiple missense mutations, rather than single ones. 12 The molecular characterization of RHD alleles was hampered in Africans by the frequent occurrence of RHD, 13 Ccde s , 14 or the concomitant presence of 2 different partial D alleles. RHD and Ccde s do not express a D antigen, yet they harbor a grossly intact RHD allele or an RHD-CE-D hybrid allele, respectively, that often interferes with RHD polymerase chain reaction (PCR) and RHD-specific sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…15 Besides RH:Ϫ18 and RH:Ϫ34 phenotypes, numerous Rhe variants are encountered in the black population. [16][17][18][19][20][21] Some variants are associated with the production of anti-e in a way similar to the production of anti-D by partial D individuals, the abnormality being restricted to the partial e situation. 12 Indeed, transfusion safety is also a problem for Dccee individuals producing alloanti-e, as the Rhe-negative RBCs that would be required are RhEpositive (e and E antigens have an antithetical relationship) and cannot be transfused to those RhE-negative individuals.…”
Section: Introductionmentioning
confidence: 99%